2020
DOI: 10.1080/17544750.2020.1807372
|View full text |Cite
|
Sign up to set email alerts
|

Nationalism and political system justification in China: differential effects of traditional and new media

Abstract: Drawing on system justification theory, this study examines the influence of political information obtained in different types of media on popular support for the Chinese political system through the mediation of nationalism. The analyses of the survey data demonstrated that obtaining political information from state-controlled media increased support for the political system through nationalist propaganda. The use of social media to obtain political information demonstrated contrasting effects. The exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Central government media are the most authoritative media. They provoke nationalism and political trust (Shen and Guo, 2013; Wang and Kobayashi, 2020). Therefore, those who used central government media more were more likely to reinforce the feeling of nationalism and be persuaded by them, adhered more to the governmental recommended measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Central government media are the most authoritative media. They provoke nationalism and political trust (Shen and Guo, 2013; Wang and Kobayashi, 2020). Therefore, those who used central government media more were more likely to reinforce the feeling of nationalism and be persuaded by them, adhered more to the governmental recommended measures.…”
Section: Discussionmentioning
confidence: 99%
“…In the COVID-19 pandemic, posts of criticism could be frequently seen. It is found that exposure to Weibo reduces nationalism and political support for the country, while WeChat users had higher level of nationalism and support for the sovereignty (Wang and Kobayashi, 2020). Therefore, users of Weibo might not be motivated to adhere to recommended measures by the government.…”
Section: Discussionmentioning
confidence: 99%
“…Although social media trust also directly impacted self-efficacy, response efficacy, and response costs, the degree was slightly lower than traditional media trust, related to social media participation and information diversification [46]. Reviews and widespread discussion of COVID-19 can still be found on social media such as Weibo, and misinformation or disinformation, including "conspiracy" may affect the proper understanding of the health, social and economic threats posed by COVID-19 [47] and may reduce political support [48]. As a result, individuals with high trust in social media did not have much motivation to comply with measures recommended by the government.…”
Section: Role Of Media Trust Of Covid-19 Vaccinationmentioning
confidence: 99%
“…The Chinese government has led a campaign of patriotism and nationalism over the past few decades (Zhao, 1998;Brady, 2002). As a result, patriotic and nationalist Chinese people show a tendency of excluding foreign cultures and upholding the current political system (Tang and Darr, 2012;Cheng et al, 2017;Wang and Kobayashi, 2021). This study examined the mechanism in which patriotism and nationalism affect public evaluations of the Chinese government's response to the pandemic.…”
Section: Discussionmentioning
confidence: 99%